Fabrication of multi-material 3D structures by the integration of direct laser writing and MEMS stencil patterning. Issue 7 (4th February 2019) - Reeves, Jeremy B.; Jayne, Rachael K.; Barrett, Lawrence; White, Alice E.; Bishop, David J.
Abstract : MEMS stencil patterning coupled with direct laser writing is used to fabricate 3D microstructures with nanoscale metallic elements. Abstract : The construction of a complex, 3D optical metamaterial challenges conventional nanofabrication techniques. These metamaterials require patterning of both a deformable mechanical substrate and an optically-active structure with ∼200 nm resolution and precision. The soft nature of the deformable mechanical materials often precludes the use of resist-based techniques for patterning. Furthermore, FIB deposition approaches produce metallic structures with considerable disorder and impurities, impairing their optical response. In this paper we discuss a novel solution to this nanofabrication challenge – the integration of direct laser writing and MEMS stencil patterning. We demonstrate a variety of methods that enable this integration and then show how one can produce optically-active, 3D metamaterials. We present optical characterization data on one of these metamaterials to demonstrate the viability of our nanofabrication approach.